Lumbosacral plexopathy: A rare long term complication of concomitant chemo-radiation for cervical cancer - Bourhafour, Imane (Gynecol Oncol Res Pract, 2015)
Radiation induced Lumbosacral plexophaty (RILP) is a rare but severe complication that has a considerable impact on quality of life. Its occurrence is rare but increasing with improved long-term cancer survival. This entity commonly results in different degrees of sensory and motor deficits. The pathophysiological mechanisms are not yet fully understood. Diagnosis of radiation myelopathy in women with gynecologic malignancies may increase with the use of concomitant chemo-radiation. This report describes the effect of this combination therapy in a 64-year-old woman with cervical carcinoma.